PRKACA: the catalytic subunit of protein kinase A and adrenocortical tumors - Berthon, Annabel S.; Szarek, Eva; Stratakis, Constantine (Frontiers in Cell and Developmental Biology, 2015)
Cyclic-AMP (cAMP)-dependent protein kinase (PKA) is the main effector of cAMP signaling in all tissues. Inactivating mutations of the PRKAR1A gene, coding for the type 1A regulatory subunit of PKA, are responsible for Carney complex and primary pigmented nodular adrenocortical disease (PPNAD). PRKAR1A inactivation and PKA dysregulation have been implicated in various types of adrenocortical pathologies associated with ACTH-independent Cushing syndrome (AICS) from PPNAD to adrenocortical adenomas and cancer, and other forms of bilateral adrenocortical hyperplasias (BAH). More recently, mutations of PRKACA, the gene coding for the catalytic subunit C alpha (Cα), were also identified in the pathogenesis of adrenocortical tumors. PRKACA copy number gain was found in the germline of several patients with cortisol-producing BAH, whereas the somatic Leu206Arg (c.617A>C) recurrent PRKACA mutation was found in as many as half of all adrenocortical adenomas associated with AICS. In vitro analysis demonstrated that this mutation led to constitutive Cα activity, unregulated by its main partners, the PKA regulatory subunits. In this review, we summarize the current understanding of the involvement of PRKACA in adrenocortical tumorigenesis, and our understanding of PKA’s role in adrenocortical lesions. We also discuss potential therapeutic advances that can be made through targeting of PRKACA and the PKA pathway.